On Comparison Theorems for Splittings of Different Semimonotone Matrices - Shu-Xin Miao; Yang Cao (Journal of Applied Mathematics)
Comparison theorems between the spectral radii of different matrices are useful tools for judging the efficiency of preconditioners. In this paper, some comparison theorems for the spectral radii of matrices arising from proper splittings of different semimonotone matrices are presented.